IBU DAN LITERASI KESEHATAN: KUNCI PENCEGAHAN STUNTING DI KELUARGA - Framesthi, Dyah Bayu; Supriatna, Dermawan; Sudrajat, Ade; Safrizal Wildan, Ari Safrizal Wildan (ABISATYA DINAMIKA ISWARA, 2024)
Stunting remains a critical public health issue, affecting children's physical and cognitive development, especially in developing countries like Indonesia. Despite global and national efforts, stunting prevalence remains significant, highlighting the need for innovative solutions. This study explores the role of maternal health literacy in preventing stunting, emphasizing the importance of understanding, accessing, and utilizing health-related information. Using a systematic literature review approach, the research analyzes findings from 13 selected studies across developing countries. Results indicate that maternal health literacy significantly impacts nutritional practices, access to health services, and the adoption of preventive measures. Community-based interventions, such as health education at local clinics (e.g., Posyandu in Indonesia) and digital health campaigns, have proven effective in improving maternal awareness and behavior. Culturally tailored strategies further enhance the success of health literacy programs. However, challenges remain in ensuring the long-term sustainability of these interventions, particularly in remote areas. This study underscores the need for inclusive, culturally sensitive, and technology-supported strategies to elevate maternal health literacy as a cornerstone for stunting prevention. Enhanced collaboration between governments, local stakeholders, and communities is essential for achieving global health targets.